RESPON PERTUMBUHAN VEGETATIF RUMPUT GAJAH (Pennisetum purpureum) TERHADAP APLIKASI LEVEL PUPUK ORGANIK DAN ANORGANIK. - Kastalani Kastalani; Maria Erviana Kusuma; Boboina Boboina (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2016)
This research aim to know the level of organic and anorganic giving best result to growth vegetatif rumput gajah (Pennisetum purpureum).  This research was design by using Completely Randomized Design with the single treatment various level organic and an organic manure (P), that is p0 = control (without organic and an organic manure), p1 = 100% urea + 0% organic manure., p2 = 75 % urea + 25 % organic manure., p3 = 50 % urea + 50 % organic manure., p4 = 25 % urea + 75 % organic manure and p5 = 0 % urea + 100 % organic manure, each treatament repeated 5 times so that there are 24 experemintal units.  The result of this research is level organic and an organic give the influence to hihg crop 6mst and 8 mst, amount of leaf 6 mst rumput gajah (Pennisetum purpureum). The component og growth show the same tendency, where the effect of organic manure given better result, coumtary with the anorganic manure